MANIPULATING THE MANDATE: EXECUTIVE INFLUENCE ON NDPS LAW AND ITS FALLOUT - Kaur , Rupneet; Singh, Parminder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Narcotic drugs and Psychotropic Substances Act, 1985 is the prime statute that regulates the law in India relating to drug use, drug abuse, possession, procedures, punishments, etc. Since its inception, it has remained a stringent special statute with the only major amendment that as made to it in 2001 vide the Narcotic Drugs and Psychotropic Substances Act (Amendment) Act, 2001. The amendment was brought with a view to rationalize the sentence structure in the Act with the introduction of concepts of small and commercial quantity in relation to Narcotic Drugs and Psychotropic Substances (NDPS). Narcotic Drugs and Psychotropic Substances (NDPS) This amendment was a constructive step of the legislature to ensure deterrent punishment for drug traffickers and comparatively less severe punishment for drug addicts using or possessing for personal use, thus trying to facilitate rehabilitation and reduce the burden on jails and courts eventually. While the courts were deciding cases by interpreting the object and reasons of this Amendment Act, the Central Government by a notification in 2009, meddled by adding an ‘explanatory note’ to the 2001 notification of the Act specifying that the weight of the entire narcotic drug or psychotropic substance along, with neutral substance, will have to be taken into consideration for determining the sentence of the accused. The current paper will discuss the validity of this notification and the confusion created by it in the adjudication of matters.